Sinergi Buah Roh dan Sila Kemanusiaan: Strategi inovatif Pembinaan Karakter di Gereja Bethel Indonesia Pemulihan Keluarga Allah - Suarni Hulu; Maria Sihombing (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
In the face of Indonesia’s escalating family crises amid rapid digital disruption and post-pandemic social recovery, this study proposes a novel “Dual-Ethos Synergy Model” that integrates the Fruits of the Spirit (Galatians 5:22–23) with the second principle of Pancasila, namely “Just and Civilized Humanity.” The study is grounded in qualitative fieldwork conducted at Gereja Bethel Indonesia Pemulihan Keluarga Allah (GBI PKA). The findings demonstrate that the integration of Christian spiritual values and civic ethics fosters restorative character formation within families and church communities. This synergy produces practical outcomes, including stronger empathy in community service, improved interpersonal relationships, and more constructive conflict resolution practices. Using data gathered through nine in-depth interviews, participant observations, and document analysis, the study addresses existing gaps in urban church discipleship by combining spiritual transformation with social responsibility and civic engagement. The proposed model also offers implications for scalable digital-hybrid ministry programs focused on family restoration and contributes to the development of contextual theological praxis within pluralistic and multicultural societies. Limitations of the study and recommendations for future research are also discussed.